A case of COVID-19 infection in a child with a tailored treatment strategy for Philadelphia chromosome-positive B-cell acute lymphoblastic leukaemia - Luchyshyn, Nataliia; Bodnarchuk-Sokhatska, Nataliia (Medycyna Paliatywna/Palliative Medicine, 2025)
Children with acute lymphoblastic leukaemia (ALL) undergoing chemotherapy are at high risk for infection due to their immunocompromised status. To date, the effect of SARS-CoV-2 on leukaemia patients is known to be variable with a generally favourable clinical course. However, therapy-related toxicity and concomitant COVID-19 manifestations may influence decision-making in each individual case. We report the case of a 13-year-old boy diagnosed with acute Philadelphia chromosome-positive B-cell ALL who experienced multiple adverse events during intensive modified and deviated chemotherapy and COVID-19 infection. The aim of the study was to demonstrate that children receiving chemotherapy should be regularly screened for SARS-CoV-2 infection in the context of the ongoing global threat of COVID-19. Because there is no standard approach to chemotherapy modification, the management of coexisting ALL and COVID-19 in paediatric patients should be individualised.